Reflective Practitioner Preparation: In the Wake of 21st Century Terrorism - Glenda Moss; Joe D. Nichols (Arizona State University, 2015)
This paper presents an example of reflective educational practice as the authors address the impact of trauma on the educational process. Multiple aspects of the educational process will be discussed: education at the national and local level as well as teacher preparation and K-12 classroom practice. The authors ground the theoretical piece in educational theory while also drawing on personal practical knowledge of experience from classroom practice. This reflective-reflexive, theory-practice inquiry method illuminated the ways that students and teachers must deal with trauma in the educational setting on a daily basis.